1998
DOI: 10.1210/jcem.83.11.5241
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Detection in Secondary Hyperparathyroidism with123I/99mTc-Sestamibi Subtraction Single Photon Emission Computed Tomography

Abstract: ABSTRACT123 I/ 99m Tc-sestamibi subtraction single photon emission computed tomography (SPECT) has been proposed to detect hyperplastic parathyroid tissue, but the clinical usefulness of this technique in secondary hyperparathyroidism is uncertain. The purpose of this study was to evaluate preoperative parathyroid localization using 123 I/ 99m Tc-sestamibi subtraction SPECT in patients with renal failure and secondary hyperparathyroidism. Nineteen patients with chronic renal failure and secondary hyperparathyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Consequently, the localization of multiglandular hyperplasia is difficult whatever the technique adopted. In patients with secondary hyperparathyroidism, US and MRI have a sensitivity of 40–50%, while preoperative 99m Tc-radiolabelled sestamibi scan has a sensitivity of 50–70% [2]. The situation is different in case of persistent or recurrent renal hyperparathyroidism, which occurs in 4% of cases, in which radionuclide scanning shows a sensitivity rate varying between 90 and 100% [6, 7, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the localization of multiglandular hyperplasia is difficult whatever the technique adopted. In patients with secondary hyperparathyroidism, US and MRI have a sensitivity of 40–50%, while preoperative 99m Tc-radiolabelled sestamibi scan has a sensitivity of 50–70% [2]. The situation is different in case of persistent or recurrent renal hyperparathyroidism, which occurs in 4% of cases, in which radionuclide scanning shows a sensitivity rate varying between 90 and 100% [6, 7, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Thus we tried to determine if the intraoperative use of a hand-held gamma detection probe can help the discovery of the hyperplastic residual gland in reoperative parathyroidectomy, where distortion of normal anatomy due to previous surgery renders surgery extremely challenging [10]. The operations in a reoperative neck have lower cure rates, higher complication rates, and take longer to perform [1, 2, 3]. In the cases described the hand-held gamma probe detection guided the dissection, restricted the operative field, avoided the exploration of unnecessary areas and allowed the localization of the residual glands, thus decreasing the risk of nerve injury because of the characteristics of the technique [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In renal hyperparathyroidism all glands are almost invariably hyperplastic. [2][3][4] The situation is completely different in the case of persistent or recurrent renal hyperparathyroidism, occurring in 4% to 10% of cases after surgery. 5 It has been suggested that initially in renal hyperparathyroidism glandular cells grow diffusely polyclonally, whereas the cells in the nodules become monoclonal and proliferate aggressively.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups perform oblique views, pin-hole and SPECT as well, showing a significant increase in the overall sensitivity of this technique [55][56][57]. It consists of the intravenous injection of 740 MBq of 99mTc-Sestamibi.…”
Section: A1) 99mtc-sestamibimentioning
confidence: 99%